2021
DOI: 10.21037/tcr-20-3408
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic stem cell microenvironment inhibits mouse glioma cell proliferation by regulating the PI3K/AKT pathway

Abstract: Background: Glioblastoma multiforme (GBM) is the most common malignant tumor of the central nervous system, accounting for 48.6% of malignant tumors. The current standard treatment plan includes the widest range of safe surgical resection, supplemented by local brain radiotherapy and temozolomide concurrent chemotherapy; this can cause serious side effects. Even so, the median survival time of GBM patients is only 8 months, and the 5-year survival rate is only 5.5%. It is imminent to find new treatments.Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…4 Meanwhile, the side effects of radiotherapy are relatively serious, which will affect the quality of life of patients. 5 Chemotherapy is a popular and feasible method to treat GBM. Nevertheless, the existence of blood−brain barrier (BBB), which is highly selective for permeability, hinders the effective delivery of chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Meanwhile, the side effects of radiotherapy are relatively serious, which will affect the quality of life of patients. 5 Chemotherapy is a popular and feasible method to treat GBM. Nevertheless, the existence of blood−brain barrier (BBB), which is highly selective for permeability, hinders the effective delivery of chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strong infiltration of GBM and unclear tumor boundaries lead to incomplete surgical resection and easy recurrence . Meanwhile, the side effects of radiotherapy are relatively serious, which will affect the quality of life of patients . Chemotherapy is a popular and feasible method to treat GBM.…”
Section: Introductionmentioning
confidence: 99%
“…The great potential of ESCs in biomedical applications lies in their ability to maintain developmental stability and differentiate into various tissues and cells ( 29 31 ). With the further exploration of ESCs, several studies have found that the malignant phenotype of tumor cells is reversed in the ESC microenvironment ( 17 , 19 ). In contrast, differentiated ESCs can contribute to the malignant phenotype of tumor cells ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference has led to an increased interest in the role of ESCs in cancer ( 17 ). Researchers found that ESCs can play a role similar to that of the early embryonic microenvironment and demonstrated that glioma cell proliferation was significantly inhibited by direct contact with murine ESCs ( 19 ). In particular, pretreatment of the microenvironment with hESCs can inhibit the aggressive or tumorigenic phenotype of melanoma cells ( 20 , 21 ), while the maximal inhibitory effects of human ESCs (hESCs) on melanoma cells can be achieved through direct cell-to-cell contact ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…He et al used ESCs to simulate the microenvironment of embryos and determined that their ability to lessen the degree of malignancy is due to downregulation of the P13K pathway. The study proved that the ESCs’ microenvironment could inhibit the PI3K pathway to promote apoptosis and thus inhibit GB proliferation [ 160 ].…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%